Optimization of Palmitic Acid Composition in Crude Oleic Acid to Provide Specifications of Titer and Cloud Point of Distillate Oleic Acid using a Flash Distiller - Muhammad Yusuf Ritonga (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2010)
Titer and cloud point of Distilled Oleic Acid is higher than is the standard on feed composition palmitic acid (C15H31COOH) or C16 11.2 %. Feed composition C16, top temperature precut and bottom main distiller column were optimized to produce DOA. A factorial design with 3 independent variables, 3 X 2 X 3, repeated twice as much, is applied to observe effects of feed composition C16 to quality parameters. In the optimum C16, feed composition at 5.20 % produced DOA with titer 6.8 oC, cloud point 5.0 oC (inside its specification).